1982
DOI: 10.1111/j.1600-0714.1982.tb00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Capping of the dental pulp mechanically exposed to the oral microflora – a 5 week observation of wound healing in the monkey

Abstract: The healing capacity of mechanically exposed and bacterially contaminated dental pulps was assessed in monkeys after capping with 2 commercial Ca(OH)2 containing compounds. One hundred eighty teeth in 7 monkeys were employed, 45 as untreated controls and 135 as treated exposures. Class V buccal cavity preparations resulting in pulpal exposure were prepared, left open to the oral cavity for 0, 1, 24 h or 7 days and employed as controls, or debrided, capped, restored with amalgam and left undisturbed for 5 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
1
2

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 14 publications
2
71
1
2
Order By: Relevance
“…3,5,9,13,32,41 Moreover, it has been emphasised that even in cases where bacterial contamination exists, the bacteria is unable to penetrate deep enough into the healthy pulp to prevent it from healing itself. 46 This capacity for self-healing appears to be the main determinant of clinical outcome in the mechanically exposed group. In both cariously exposed groups 1 and 2, pulpotomy success rates were higher for teeth restored with SSCs than for teeth restored with amalgam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,9,13,32,41 Moreover, it has been emphasised that even in cases where bacterial contamination exists, the bacteria is unable to penetrate deep enough into the healthy pulp to prevent it from healing itself. 46 This capacity for self-healing appears to be the main determinant of clinical outcome in the mechanically exposed group. In both cariously exposed groups 1 and 2, pulpotomy success rates were higher for teeth restored with SSCs than for teeth restored with amalgam.…”
Section: Discussionmentioning
confidence: 99%
“…35 Numerous studies have shown that ZOE, which was used in this study as a base material, has good sealing ability and antibacterial properties. 1,8,32,46,49,50,56 It may therefore be suggested that ZOE used under restorations may prevent bacterial contamination either through its sealing ability and/or its antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
“…It is the state of the pulp and the degree of bacterial contamination that enters the pulp, rather than the size of the exposure, that largely determines the prognosis of pulp capping (33,34). The technique with which the exposure is created may also affect pulpal healing.…”
Section: Lim and Kirkmentioning
confidence: 99%
“…In animal studies, mechanical exposure of the pulp followed by exposure to the oral environment for up to 24 h could be successfully capped (29,33,34), although healing took longer (29). A study in monkeys indicates that when the pulp is exposed to the oral environment for more than 24 h before capping, the prognosis declines (34), because bacterial contamination becomes excessive, although a more recent study in monkeys where pulp exposures were left untreated for up to 7 days stifl healed successfully (36).…”
Section: Bactariai Contaminationmentioning
confidence: 99%
See 1 more Smart Citation